Suppression of Supersonic Cavity Oscillations Using Pulsed Upstream Mass Injection - Weipeng Li (International Journal of Aerospace Engineering)
Pulsed upstream mass injection is examined to suppress supersonic cavity oscillations. The efficiency and physics of the noise control are investigated by large-eddy simulations of a turbulent flow (M∞=2.0, ReD=105) past a rectangular cavity with a length-to-depth ratio of 2. Results show that the pulsed mass injection behaves less effectively in reducing the cavity oscillations than the steady one. The primary reason is that the pulsed mass injection is ineffective in lifting up the cavity shear layer and in suppressing the turbulent fluctuations in the shear layer. It concluded that breakup of the large-scale vorticial structures into a smaller length scale reveals direct links existing between the large-scale vortices and the radiation of the cavity resonances.